The spatial cell biology of host control in bacteriocyte-associated symbioses - Dustin Dial; Javier Andres Tejeda-Mora; Filip Husnik (Current Opinion in Insect Science, 2026)

Pathways to an integrated understanding of marine environments and ecosystems in the Asia-Pacific Region - Hanani Adiwira; Sayaka Yasunaka; Jamie M. Kass; Ayşe H. O. Açıkbaş; Sekar Adiningsih; Emma Gairin; Hovaldo B. C. Ilham; Elisa Lahcene; Yanguo Li; Gaku Nishihira; Paula Peñalver-Pereira; Florence M. P. Sie; et al. (Frontiers in Marine Science, 2025)
The Asia-Pacific Region (APR) encompasses a vast geographical area rich in marine biodiversity that plays critical roles in global ecological stability and climate regulation, but it also faces daunting challenges in maintaining these roles under global change. Environmental dynamics in the APR manifest regularly over a range of timescales, including storms, earthquakes, floods, and extreme heat events. Further, coastal and marine ecosystems, including extensive commercial fisheries and coral reefs, are under threat from intense resource extraction and increasingly frequent marine heatwaves. Knowledge gaps for understanding these complex systems are aggravated by substantial barriers to cross-national efforts caused by the region’s vast diversity of cultures, languages, socioeconomics, politics, and management practices. Effective management of marine resources in the APR will necessitate multidisciplinary research based on continuous, region-wide observations supported by robust collaborations. In 2023, we gathered APR researchers across disciplines to discuss these issues and find solutions during a thematic seminar and workshop program at Tohoku University in Japan. Based on the results of this program, we present a review of the current state of APR marine ecosystems, raise key questions addressable through multidisciplinary approaches, and identify future priorities for the region. We conclude that sustaining biodiversity, ecosystem functions, and climate resilience in the APR will depend on stronger interdisciplinary collaboration, better integration of biological and geophysical data, and broader access to marine observations. These efforts are both urgent and essential for supporting better science-based policy decisions to address the escalating effects of global change on marine systems across the region.

Phylogenomics shows that novel tapeworm-like traits of haplozoan parasites evolved from within the Peridiniales (Dinoflagellata) - Eunji Park; Elizabeth Cooney; Yong Heng Phua; Takeo Horiguchi; Filip Husnik; Patrick Keeling; Kevin Wakeman; Brian Leander (Molecular Phylogenetics and Evolution, 2023)

Bacterial communities and toxin profiles of Ostreopsis (Dinophyceae) from the Pacific island of Okinawa, Japan - Yong Heng Phua; Javier Tejeda; Michael C. Roy; Filip Husnik; Kevin C. Wakeman (European Journal of Protistology, 2023)

Sex‐specific expression and DNA methylation in a species with extreme sexual dimorphism and paternal genome elimination - Stevie A. Bain; Hollie Marshall; Andrés G. de la Filia; Dominik R. Laetsch; Filip Husnik; Laura Ross (Molecular Ecology, 2021)
Phenotypic differences between sexes are often mediated by differential expression and alternative splicing of genes. However, the mechanisms that regulate these expression and splicing patterns remain poorly understood. The mealybug, Planococcus citri , displays extreme sexual dimorphism and exhibits an unusual instance of sex‐specific genomic imprinting, paternal genome elimination (PGE), in which the paternal chromosomes in males are highly condensed and eliminated from the sperm. Planococcus citri has no sex chromosomes and both sexual dimorphism and PGE are predicted to be under epigenetic control. We recently showed that P . citri females display a highly unusual DNA methylation profile for an insect species, with the presence of promoter methylation associated with lower levels of gene expression. Here, we therefore decided to explore genome‐wide differences in DNA methylation between male and female P . citri using whole‐genome bisulphite sequencing. We identified extreme differences in genome‐wide levels and patterns between the sexes. Males display overall higher levels of DNA methylation which manifest as more uniform low levels across the genome. Whereas females display more targeted high levels of methylation. We suggest these unique sex‐specific differences are due to chromosomal differences caused by PGE and may be linked to possible ploidy compensation. Using RNA‐Seq, we identify extensive sex‐specific gene expression and alternative splicing, but we find no correlation with cis ‐acting DNA methylation.

Dynamic recruitment of amino acid transporters to the insect/symbiont interface - Rebecca P. Duncan; Filip Husnik; James T. Van Leuven; Donald G. Gilbert; Liliana M. Dávalos; John P. McCutcheon; Alex C. C. Wilson (Molecular Ecology, 2014)
Symbiosis is well known to influence bacterial symbiont genome evolution and has recently been shown to shape eukaryotic host genomes. Intriguing patterns of host genome evolution, including remarkable numbers of gene duplications, have been observed in the pea aphid, a sap‐feeding insect that relies on a bacterial endosymbiont for amino acid provisioning. Previously, we proposed that gene duplication has been important for the evolution of symbiosis based on aphid‐specific gene duplication in amino acid transporters ( AAT s), with some paralogs highly expressed in the cells housing symbionts (bacteriocytes). Here, we use a comparative approach to test the role of gene duplication in enabling recruitment of AAT s to bacteriocytes. Using genomic and transcriptomic data, we annotate AAT s from sap‐feeding and non sap‐feeding insects and find that, like aphids, AAT gene families have undergone independent large‐scale gene duplications in three of four additional sap‐feeding insects. RNA ‐seq differential expression data indicate that, like aphids, the sap‐feeding citrus mealybug possesses several lineage‐specific bacteriocyte‐enriched paralogs. Further, differential expression data combined with quantitative PCR support independent evolution of bacteriocyte enrichment in sap‐feeding insect AAT s. Although these data indicate that gene duplication is not necessary to initiate host/symbiont amino acid exchange, they support a role for gene duplication in enabling AAT s to mediate novel host/symbiont interactions broadly in the sap‐feeding suborder Sternorrhyncha. In combination with recent studies on other symbiotic systems, gene duplication is emerging as a general pattern in host genome evolution.